2021
DOI: 10.5944/rppc.29038
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between coping, anxiety and depression among a Mexican sample during the onset of the Covid-19 pandemic

Abstract: The coping strategies used during the COVID-19 pandemic could explain why certain individuals experience higher levels of anxiety and depression than others. A sample of 747 subjects completed an ad-hoc questionnaire on their habits during the pandemic, the Stress Coping Questionnaire (SCQ) focused on COVID-19; the Beck Anxiety Inventory (BAI) and the Beck Depression Inventory (BDI). High percentages of the sample recorded moderate and severe levels of anxiety (45.38%) and depression (32.13%), which were highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
1
1
0
2
Order By: Relevance
“…A recent meta-analysis reported by Salari et al (2020) based on 17 studies of the general population found that the prevalence of anxiety and depression, as a result of the COVID-19 pandemic, was 31.9 and 33.7%, respectively. Similar results have been found in studies of the general population conducted in Spain (Hidalgo et al, 2020;Sandín et al, 2020cSandín et al, , 2021Gutiérrez-Hernández et al, 2021) and Hispanic American countries (Andrades-Tobar et al, 2021;Mestas et al, 2021) since the COVID-19 pandemic, as well as in children and adolescents (Gómez-Becerra et al, 2020;Orgilés et al, 2020bOrgilés et al, , 2021Pedreira, 2020). The existing literature on the impact of COVID-19 in adolescents is generally limited, and evidences the relevance of researching this issue (e.g., Muzi et al, 2021), including the role of emotion regulation strategies (Velotti et al, 2021).…”
Section: Introductionsupporting
confidence: 79%
“…A recent meta-analysis reported by Salari et al (2020) based on 17 studies of the general population found that the prevalence of anxiety and depression, as a result of the COVID-19 pandemic, was 31.9 and 33.7%, respectively. Similar results have been found in studies of the general population conducted in Spain (Hidalgo et al, 2020;Sandín et al, 2020cSandín et al, , 2021Gutiérrez-Hernández et al, 2021) and Hispanic American countries (Andrades-Tobar et al, 2021;Mestas et al, 2021) since the COVID-19 pandemic, as well as in children and adolescents (Gómez-Becerra et al, 2020;Orgilés et al, 2020bOrgilés et al, , 2021Pedreira, 2020). The existing literature on the impact of COVID-19 in adolescents is generally limited, and evidences the relevance of researching this issue (e.g., Muzi et al, 2021), including the role of emotion regulation strategies (Velotti et al, 2021).…”
Section: Introductionsupporting
confidence: 79%
“…Estos datos son congruentes con la idea de que estas diferencias se deben a los roles asumidos por hombres y mujeres a lo largo de la evolución, que podría derivar en una divergencia cualitativa en la forma en que cada uno integra la información emocional para apoyar los procesos de toma de decisiones (Christov-Moore et al, 2014). Estas diferencias, además, podrían estar en la base explicativa de los mayores niveles mostrados por las mujeres (frente a los hombres), en ansiedad y depresión durante la pandemia (Mestas et al, 2021;Sandín et al, 2020). Por otro lado, las personas que han sido hospitalizadas reportan mayores niveles de miedo interiorizado, aunque los grupos de comparación son muy desiguales en el número y habría que tomar con precaución estos resultados (véase tabla 4).…”
Section: Discusión Y Conclusionesunclassified
“…Durante este tiempo se han construido algunas escalas para su medida (por ejemplo, Ahorsu et al, 2020: FCV-19S), que han evidenciado una relación directa entre miedo a la pandemia, estrés, ansiedad y, en menor medida, depresión (Rodríguez-Hidalgo et al, 2020). También se ha observado que las mujeres y los jóvenes presentan mayores niveles de estrés, ansiedad, depresión y miedo a la COVID-19 (Mestas et al, 2021;Sandín et al, 2020). No obstante, se ha prestado poca atención a la relación entre miedo a la pandemia y variables como la percepción de riesgo y la empatía, que, por separado y en interacción, podrían condicionar la adherencia de la población a las normas de prevención (uso de mascarillas, distancia social, aislamiento preventivo), así como la prevalencia de trastornos mentales como la ansiedad y la depresión.…”
Section: Introductionunclassified
“…The COVID19 pandemic led us to wonder about the psychological impact it has had and will have in the short, medium, and long term due to the lockdown and all their implications. Several studies have shown how mental health can be affected during a lockdown period (Brooks et al, 2020;Maekelae et al, 2020;Prati, 2021;Veer et al, 2021) and the COVID19 pandemic in general (Bedoya Cardona et al, 2021;BedoyaCardona, ArboledaGil et al, 2022;BedoyaCardona, HansenRodríguez et al, 2022;Luo et al, 2020;Mestas et al, 2021;Salari et al, 2020;Sandín et al, 2020). Therefore, it is important to get to know perceptions, beliefs, emotions, and reactions regarding lockdown, since a measure of such magnitude and length of time, even if taken for the good of the population, can usually generate psychological distress in people .…”
Section: Introductionmentioning
confidence: 99%